Tingkat Literasi Keuangan Manajemen Terhadap Penangangan Risiko Kerugian Pada Perusahaan Air Minum Tirta Karajae Kota Parepare Melalui Pemahaman Tentang Risk Manajement - Imran Rosadi; Sri Resky Handayani (Economics and Digital Business Review, 2024)
This research aims to determine the influence of the level of Financial Literacy in terms of Financial Knowledge, Financial Attitude and Financial Behavior Management on handling the risk of loss at the Tirta Karajae Drinking Water Company (PAM). Parepare City, to determine the influence of the level of understanding of Risk Management on Handling the Risk of Loss at the Tirta Karajae Drinking Water Company (PAM) Parepare City. To determine the influence of the level of Financial Literacy in terms of Financial Knowledge, Financial Attitude and Financial Behavior of Management on the Level of Understanding of Risk Management at the Tirta Karajae City Drinking Water Company (PAM). Parepare. and to determine the influence of the level of Financial Literacy in terms of Financial Knowledge, Financial Attitude and Financial Behavior of Management if mediated by an Understanding of Risk Management on handling the risk of loss at Drinking Water Companies ( PAM) Tirta Karajae Parepare City. The results obtained from this research are that Financial Knowledge and Financial Attitude of Management have a positive but not significant impact, while Management's Financial Behavior and Level of Understanding of Risk Management have a positive and significant impact on Handling the Risk of Losses at the Tirta Karajae Drinking Water Company (PAM) Parepare City. The level of financial knowledge and level of financial behavior of management has a positive and significant influence, while the financial attitude of management has a positive influence but does not have a significant impact on the level of understanding of risk management at drinking water companies (PAM). ) Tirta Karajae Parepare City. The level of financial knowledge and level of financial behavior of management has a positive and significant influence on the management's financial attitude, while the financial attitude of management has a positive influence but does not have a significant impact on handling the risk of loss at the Tirta Karajae Drinking Water Company (PAM). Parepare City after being mediated by the Level of Understanding of Risk Management